POLITICAL PARADIGM OF CONVENTIONAL ECONOMICS AND ISLAMIC ECONOMICS: INDONESIAN SHARIA BANK DISCOURSE - Witro, Doli (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2021)
This article discusses the paradigm of Islamic political economy and conventional political economy by looking at the discourse of Indonesian sharia banks. This article aims to find out how the political economy that occurs in Indonesian sharia banks. This article is qualitative library research. The data in this study were obtained from library materials such as books, journals, and so on related to the problems studied, namely the conventional political economy paradigm and the Islamic political economy paradigm. The data collection technique used is to collect as much data as possible about the problems studied through the internet and library websites. The data writing technique used is a data analysis technique known by Miles et al., namely data condensation, data presentation, and drawing conclusions. The analysis results show that the differences between Islamic and conventional political economy paradigms are seen in the unification (religion and economic activity) by Islamic economics and separation (religion and economic activity) by conventional economics. The dominance of the conventional economic system, represented by the capitalist and socialist economic system in the world economy, especially Indonesia, does not dampen the significant development of the Islamic economic system, which is agreed upon by various parties.